Intranasal pleomorphic adenoma: An unexpected diagnosis - Bani, Amina; Nechi, Salwa; Douggaz, Amel; Noomen, Imène; Kharrat, Ghada; Chelbi, Emna (Biomedicine & Healthcare Research, 2025)
Pleomorphic adenoma is a heterogeneous benign tumor of the salivary glands, with the parotid gland being the most common site of occurrence. However, its presence in the minor salivary glands is relatively rare. Here, we report the case of a 57-year-old man diagnosed with a nasal pleomorphic adenoma. In this context, we aim to clarify the epidemiological, diagnostic, therapeutic, and prognostic characteristics of nasal pleomorphic adenoma.